ETHICAL DIMENSIONS OF ISLAMIC FINANCE AND THEIR RELEVANCE IN CONTEMPORARY BUSINESS PRACTICES - Baloch, Babruk Aijaz; Chimenya, Andrew (International Journal of Islamic Banking and Finance Research, 2023)
In the vast tapestry of global financial systems, Islamic finance emerges as a paragon of ethical praxis, steeped in the venerable tenets of Shariah law. The essence of this research is the exploration of these profound ethical underpinnings and their resonance in the contemporary mercantile milieu. The study takes a deep dive into the historical evolution of Islamic finance to highlight its core values of fairness, societal stewardship, and sustainable growth. These values make it a compelling alternative to the criticisms often levelled at conventional monetary systems. This research methodology adopts a systematic literature review approach, sourcing information from peer-reviewed articles, books, conference papers, and reports from recognised financial bodies. The culmination of this endeavour reveals an intricate interplay between the time-honoured ethics of Islamic finance and its manifestation in the modern economic realm. The introduction suggests that Islamic finance offers moral rectitude by championing risk-sharing and avoiding interest-driven transactions in today's globalised commerce.JEL Classification Codes: G21, G20, Z12, P51, D63.